The Effectiveness of STEM-PjBL-Based Mathematics Student Worksheets on the Cognitive Learning Outcomes of Grade V MI Students - Veramica Futri, Feni; Agusdianita , Neza; Widi Winarni, Endang (ATTA`DIB, 2025)
This study aims to develop and test the feasibility and effectiveness of Student. Worksheet (LKPD) based on Science, Technology, Engineering, and Mathematics (STEM) integrated with the Project-Based Learning (PjBL) model in improving students' cognitive learning outcomes on the topic of the perimeter and area of flat shapes. The development of the LKPD is carried out using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research method used is Research and Development (R&D). Validation was carried out by material experts, language experts, and graphic design experts, and tested on fifth-grade students at MIN 05 Seluma to assess its effectiveness. The validation results showed that the developed LKPD is highly feasible, with validation scores from material experts at 0.94, language experts at 0.96, graphic design experts at 0.92, and item validation at 0.95. The effectiveness test demonstrated an improvement in students' learning outcomes, with an average N-Gain score of 78.48%, which falls into the effective category. Thus, this STEM-based LKPD integrated with the PjBL model is declared valid, effective, and suitable to be used as a learning tool to enhance students' understanding of the concepts of perimeter and area of plane figures.